LANGUAGE ACHIEVEMENTS OF FINAL GRADES OF PRIMARY SCHOOL PUPILS IN THE REPUBLIC OF SERBIA IN THE FIELD OF GERMAN AS A SECOND FOREIGN LANGUAGE (Živi jezici: Journal for Foreign Languages and Literatures, 2018)
The paper presents an analysis of the results of research in the field of receptive language skills and grammatical-lexical knowledge, conducted in the final grades of primary schools in the Republic of Serbia in which German is taught as a second foreign language. The obtained results are a consequence of changes in foreign language curricula at the primary school level and are interpreted in terms of motivation, taking into account factors that are sociolinguistically oriented, such as social environment and the value of foreign language, and then individual factors, such as personal affinities, degree of efficiency, and goal of language learning. The aim of this paper is to point out the negative consequences of the decision to reduce the number of classes in second foreign language, as well as the selection and approval of teaching materials, curriculum content, which, among other things, led to a decline in motivation among students. they inevitably acquired the implicit status of a more complicated, even less important language.
Keywords: German as a second FL; testing; evaluation; language competencies; number of classes